Inovasi E-Service Administrasi Kependudukan dalam Mendukung Pelayanan Publik Digital - Nur Aini Mayasiana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Jember, 2026)
Digital transformation encourages local governments to provide public services that are more effective, efficient, and easily accessible to the community. One of the digital service innovations developed by the Department of Population and Civil Registration of Jember Regency is the J-Lahbako application as an electronic-based population administration service. This study aims to analyze the innovation of population administration e-service through the J-Lahbako application in supporting digital public services in Jenggawah District, Jember Regency. This research employed a qualitative descriptive method with data collection techniques through observation, interviews, documentation, and focus group discussions (FGD). The research informants consisted of the Department of Population and Civil Registration of Jember Regency, district government, village government, J-Lahbako operators, and the community. The results showed that the J-Lahbako application provides convenience in online population administration services, accelerates service processes, increases time efficiency, and expands service access to the village level. This digital service innovation also supports the creation of more responsive and modern public services. However, the implementation of the J-Lahbako application still faces several obstacles, such as network system disruptions and the limited ability of operators to understand system updates. Therefore, it is necessary to improve human resource capacity, strengthen information technology systems, and conduct continuous socialization so that digital-based population administration services can operate more optimally.